2010
DOI: 10.14236/ewic/ease2010.6
|View full text |Cite
|
Sign up to set email alerts
|

Experiences Conducting Systematic Reviews from Novices’ Perspective

Abstract: Background: A systematic review (SR) is a sound methodology for collecting evidence on a research topic of interest and establishing the context of future research. Unlike ordinary or even expert literature reviews, SRs are systematic thus increasing the confidence in the findings from the previous published literature. SRs can be carried out by both experienced and novice researchers; however, while expert researchers" experiences with conducting SRs are important for improving the SR body of knowledge, we be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…The other two categories related to students were: • Master students (11 (39.2%) -S4 [19]; S7 [22]; S8 [23]; S16 [29]; S17 [30]; S18 [31]; S23 [35]; S25 [37]; S26 [9]; S27 [38]; S28 [39]); and • Ph.D. students (8 (28.5%) -S9 [24]; S10 [7]; S12 [26]; S15 [12]; S16 [29]; S24 [36]; S27 [38]; S28 [39]). Only 4 studies (14.2%) assessed the use of EBSE by SLR experts (S10 [7]; S11 [25]; S15 [12]; S19 [32]). Some categories that were identified are strongly related, for instance, [18]; S4 [19]; S5 [20]; S6 [21]; S8 [23]; S10 [7]; S12 [26]; S13 [27]; S22 [34]; S23 [35]; S24 [36]; S25 [37]; S26 [9]; and S27 [38] Journal 9 (32.1%) -S7 [22]; S11 [25]; S14 [28]; S15 [12]; S17 [30]; S18 [31]; S19 [32]; S21 [8]; and S28 [39] Symposium 4 (14.2%) -S1…”
Section: Purposes Of Ebse In An Academic Context (Rq2)mentioning
confidence: 99%
See 2 more Smart Citations
“…The other two categories related to students were: • Master students (11 (39.2%) -S4 [19]; S7 [22]; S8 [23]; S16 [29]; S17 [30]; S18 [31]; S23 [35]; S25 [37]; S26 [9]; S27 [38]; S28 [39]); and • Ph.D. students (8 (28.5%) -S9 [24]; S10 [7]; S12 [26]; S15 [12]; S16 [29]; S24 [36]; S27 [38]; S28 [39]). Only 4 studies (14.2%) assessed the use of EBSE by SLR experts (S10 [7]; S11 [25]; S15 [12]; S19 [32]). Some categories that were identified are strongly related, for instance, [18]; S4 [19]; S5 [20]; S6 [21]; S8 [23]; S10 [7]; S12 [26]; S13 [27]; S22 [34]; S23 [35]; S24 [36]; S25 [37]; S26 [9]; and S27 [38] Journal 9 (32.1%) -S7 [22]; S11 [25]; S14 [28]; S15 [12]; S17 [30]; S18 [31]; S19 [32]; S21 [8]; and S28 [39] Symposium 4 (14.2%) -S1…”
Section: Purposes Of Ebse In An Academic Context (Rq2)mentioning
confidence: 99%
“…Only 4 studies (14.2%) assessed the use of EBSE by SLR experts (S10 [7]; S11 [25]; S15 [12]; S19 [32]). Some categories that were identified are strongly related, for instance, [18]; S4 [19]; S5 [20]; S6 [21]; S8 [23]; S10 [7]; S12 [26]; S13 [27]; S22 [34]; S23 [35]; S24 [36]; S25 [37]; S26 [9]; and S27 [38] Journal 9 (32.1%) -S7 [22]; S11 [25]; S14 [28]; S15 [12]; S17 [30]; S18 [31]; S19 [32]; S21 [8]; and S28 [39] Symposium 4 (14.2%) -S1 [16]; S9 [24]; S16 [29]; and S20 [33] undergraduate and Masters (e.g. S16 [29]); Masters and Ph.Ds.…”
Section: Purposes Of Ebse In An Academic Context (Rq2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dybå et al [8] consider "normal" meta-analytic approaches to be of limited use for software engineering only and, hence, report their experience from applying diverse study types in a systematic review; a mixed-method approach similar to the practices reported in the present article. Riaz et al [45] provide a different perspective in their report and mention experts and novices having a different perception of the systematic review process and its challenges. The present article also addresses this point by providing examples, reusable assets like research questions or in-/exclusion criteria, and a detailed elaboration on selected practices and a demonstration of their use.…”
Section: Ref Key Contributionsmentioning
confidence: 99%
“…The review follows Kitchenham and Charter's guidelines for systematic literature reviews [10]. Furthermore, the review takes into account insights from practical experiences with systematic reviews [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%